2009
DOI: 10.1097/aln.0b013e318195b4fe
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Postischemic Neurogenesis in Rats with Cerebral Ischemia and Propofol Anesthesia

Abstract: Background: Postischemic endogenous neurogenesis can be dose-dependently modulated by volatile anesthetics. The intravenous anesthetic propofol is used during operations with a risk of cerebral ischemia, such as neurosurgery, cardiac surgery, and vascular surgery. The effects of propofol on neurogenesis are unknown and, therefore, the object of this study.Methods: Eighty male Sprague-Dawley rats were randomly assigned to treatment groups with propofol administration for 3 h: 36 mg · kg ؊1 · h ؊1 propofol with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
(32 reference statements)
1
11
1
Order By: Relevance
“…34 Finally, the preclinical data do not support a difference between propofol and the halogenated agents in terms of putative prevention of neuropathy, as both may act on the peripheral fibres 35,36 and may even have some neuroprotective effects. 37,38 Although it might be possible to explain the discrepancy between our results and those of Cho et al 10 by examining the mechanisms, it may also be explained by different methodologies. Our design had a greater sample size, standardised times of measurement of PPSP and a multicentre setting.…”
Section: Discussioncontrasting
confidence: 69%
“…34 Finally, the preclinical data do not support a difference between propofol and the halogenated agents in terms of putative prevention of neuropathy, as both may act on the peripheral fibres 35,36 and may even have some neuroprotective effects. 37,38 Although it might be possible to explain the discrepancy between our results and those of Cho et al 10 by examining the mechanisms, it may also be explained by different methodologies. Our design had a greater sample size, standardised times of measurement of PPSP and a multicentre setting.…”
Section: Discussioncontrasting
confidence: 69%
“…46,47 Such controversy may be due to confounding variables in the use of animal models. 48,49 In an attempt to reduce such variables, we chose to study neural progenitor cells in vitro. Our results suggested that at clinically relevant concentrations of propofol, proliferation contributed more to the increased cell viability than differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Propofol has been reported to be beneficial in focal [109, 110], hemispheric [111], and global [112-114] ischemic insults. These positive results have been countered by other work, which failed to detect an effect on outcome in vivo [115-117] or in vitro [53]. α-2-agonists are a class of compounds including dexmedetomidine, clonidine, and xylazine.…”
Section: Ischemic Outcomementioning
confidence: 97%